Empowering the Millennial Generation Based on Digital Leadership at the Muhammadiyah Students Association In Mataram City - Pratama, Inka Nusamuda; Lestanata, Yudhi; Hidayat, Rahmad; Afriansyah, Indra; Sucipto, Adi; Mursalim, Mursalim (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2025)
The millennial generation has a strategic role in developing leadership in the digital era, especially in student organizations such as the Muhammadiyah Student Association (IMM) of Mataram City. However, digital leadership skills are still a challenge for many students due to a lack of understanding of the use of technology in leadership. This community service activity aims to improve the digital leadership capacity of IMM Mataram City members through counselling, practice and interactive methods. This activity was attended by 16 IMM Mataram City members who actively participated in the entire training series. The activity results showed that participants gave an excellent assessment of the activity's benefits, the material's quality, and the interaction with the presenters. The satisfaction survey noted that participants felt more prepared to face the challenges of leadership in the digital era and were able to apply new skills in their organizations. These findings indicate that the activity contributed to forming an IMM Mataram City that is innovative, adaptive, and ready to face future digital leadership challenges.